Establishment of data intellectual property rights and anti-monopoly regulation in China - Han, Xiao; Nabeel Mahdi Althabhawi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Data drives innovation, expands markets, and improves efficiency, enabling companies to better meet market demands. In the AI market, data has even become a significant barrier to market entry. Currently, data laws primarily focus on personal information protection and data security in China. Despite recognizing the value of data, current legislation lacks definitions and protections for data rights, leading to data misuse and monopolistic practices, highlighting the urgent need for specialized intellectual property protection and regulatory legislation. Through doctrinal research and comparative analysis, this study evaluates the characteristics of data, existing legal frameworks, and relevant cases, comparing them with the European Union’s data legal framework. The aim is to clarify the concept of data IP, fill the legislative void in data IP protection and antitrust regulation, and propose recommendations to enhance digital IP protection and anti-monopoly regulation. Recognizing data as IP is the best approach to accommodate its public and proprietary nature, effectively protecting data innovation. Thus, there is an urgent need to establish a comprehensive and forward- looking legal framework to protect data as IP and prevent data monopolies.